Origins and Molecular Mechanisms Underlying Renal Vascular Development - Yusuke Nishimura; Sanshiro Hanada (Kidney360, 2024)
Kidneys play a crucial role in maintaining homeostasis within the body, and this function is intricately linked to the vascular structures within them. For vascular cells in the kidney to mature and function effectively, a well-coordinated spatial alignment between the nephrons and complex network of blood vessels is essential. This arrangement ensures efficient blood filtration and regulation of the electrolyte balance, blood pressure, and fluid levels. Additionally, the kidneys are vital in regulating the acid-base balance and producing hormones involved in erythropoiesis and blood pressure control. This article focuses on the vascular development of the kidneys, summarizing the current understanding of the origin and formation of the renal vasculature, and the key molecules involved. A comprehensive review of existing studies has been conducted to elucidate the cellular and molecular mechanisms governing renal vascular development. Specific molecules play a critical role in the development of renal vasculature, contributing to the spatial alignment between nephrons and blood vessels. By elucidating the cellular and molecular mechanisms involved in renal vascular development, this study aims to advance renal regenerative medicine and offer potential avenues for therapeutic interventions in kidney disease.